Norms Affect Prospective Causal Judgments. Issue 1 (7th January 2021) - Henne, Paul; O'Neill, Kevin; Bello, Paul; Khemlani, Sangeet; De Brigard, Felipe
Abstract: People more frequently select norm‐violating factors, relative to norm‐conforming ones, as the cause of some outcome. Until recently, this abnormal‐selection effect has been studied using retrospective vignette‐based paradigms. We use a novel set of video stimuli to investigate this effect for prospective causal judgments—that is, judgments about the cause of some future outcome. Four experiments show that people more frequently select norm‐violating factors, relative to norm‐conforming ones, as the cause of some future outcome. We show that the abnormal‐selection effects are not primarily explained by the perception of agency (Experiment 4). We discuss these results in relation to recent efforts to model causal judgment.